TEORI KECURANGAN, FRAUD AWARENESS DAN METODOLOGI UNTUK MENDETEKSI KECURANGAN PELAPORAN KEUANGAN - Lusy Suprajadi (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Fraud in financial reporting may result in material misstatement. Auditor has a responsibility to detect fraud before concludes that financial statements are presented fairly. Therefore auditor must have fraud awareness that fraud may occur and learn how fraudster commits fraud. Fraud theory can explain why people commit fraud. Fraud happens because of rationalization, pressure, and opportunity. Auditor has to conduct audit in a systematic manner through precise methodology. This paper describes how to detect fraudulent financial reporting through understanding fraud theory, fraud awareness and methodology.